Pengaruh Gaya Kepemimpinan, Komitmen Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Kasus di PT. Safari Salatiga) - Saputro, Danang Tri, Drs. Sri Padmantyo, MBA (2017)
The purpose of this study to determine the working style of leadership, commitment, work environment on employee performance employee. Used as a sample of 60 respondents in the company's employee population that is actively working. Based on the results of the analysis can be concluded that demonstrate leadership style variable, commitment and work environment affect the performance of individual employees. This shows that the variable of leadership style, commitment and working environment significantly affect the performance of the employee satisfaction together. In an effort to improve employee performance with regard emphatic leadership, democratic and provides the opportunity to subordinates to argue. Noting the commitment of the organization to create binding regulations affecting employees in the work performance of employees and pay attention to the work environment that is safe, comfortable and orderly.